Trans-áridas: cartografando relatos performáticos de mulheres travestis e transexuais do semiárido baiano - Santos , Denyse de Almeida dos (2023)
The dissertation explores the invisibility and experiences of transvestites and transgender individuals living in the semi-arid region of Bahia, a territory still marked by cissexist traditions. In this context, these individuals face significant challenges in expressing their ways of life and surviving in the small rural and urban towns of this arid region. The researcher, who is herself a transvestite residing in this territory, shares her life and personal journey as a conceptual and non-fictional character, highlighting the subjective constructions that led her to become a transvestite. Furthermore, she joins other transvestites to form a kind of human cartography, where each one recounts their experiences and escape strategies within the challenging context of the semi-arid Bahian hinterlands, using performances as a form of expression. These narratives challenge the entrenched stereotypes in the region, which is often still associated with the notion of "cabra-macho," and contribute to the (re)construction of a performative and transvestite semi-arid, allowing for authentic expression and full existence of transvestites and transgender individuals in this geographical space. The dissertation underscores the importance of visibility and empowerment for these marginalized communities, as well as their capacity for resistance and reinvention in a socially challenging environment.